2006
DOI: 10.1097/01.mco.0000196143.72985.9a
|View full text |Cite
|
Sign up to set email alerts
|

Is glycine effective against elevated blood pressure?

Abstract: The use of glycine to lower high blood pressure could have a significant clinical impact in patients with the metabolic syndrome and with limited resources. On the other hand, more studies are needed to explore the beneficial effect of glycine in other models of hypertension and to investigate possible side-effects of treatment with glycine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…Many efforts have been made to reverse endothelial dysfunction or improve overall endothelial function (Durrant et al 2009;Idris et al 2012). To this end, many investigations have demonstrated that glycine has antioxidant and anti-inflammatory activities (Brawley et al 2004;El-Hafidi et al 2006;Alarcon-Aguilar et al 2008). Therefore, we investigated whether this amino acid could be useful in treating age-associated vascular endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many efforts have been made to reverse endothelial dysfunction or improve overall endothelial function (Durrant et al 2009;Idris et al 2012). To this end, many investigations have demonstrated that glycine has antioxidant and anti-inflammatory activities (Brawley et al 2004;El-Hafidi et al 2006;Alarcon-Aguilar et al 2008). Therefore, we investigated whether this amino acid could be useful in treating age-associated vascular endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…M, mol/L. glutathione (GSH) pathway by glycine has been demonstrated to reduce high blood pressure in a model of metabolic syndrome (El-Hafidi et al 2006). In this sense, Sekhar et al (2011) found that glycine decreased the oxidative stress associated with aging by acting as a precursor in GSH synthesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This discrepancy between men and women may indicate that the observed significant associations between glycine intake and total and ischemic stroke mortality in men without a prior history of hypertension were by chance. Experimental studies have not supported that glycine could raise blood pressure; rather, some of them suggested favorable effects of glycine on blood pressure (26). Glycine is involved in the pathway for the storage of iron (27).…”
Section: Discussionmentioning
confidence: 98%
“…the present findings suggest that the maternal intake of appropriate amounts of protein, in proportion to total caloric intake, is important for protection against the development of cVd risk factors in adult offspring. Protein is composed of various amino acids, among which glycine given to pregnant rats on a low-protein diet has been reported to reduce blood pressure [28,29] and improve vascular function [30]. at present we have no evidence for the contribution of glycine to the reduction of CVD risk factors in HPD-UN offspring; however, an analysis of changes in specific amino acids in this animal model is now under way.…”
Section: Discussionmentioning
confidence: 93%